2010
DOI: 10.1002/app.31778
|View full text |Cite
|
Sign up to set email alerts
|

Water absorbance and thermal properties of sulfated wheat gluten films

Abstract: Wheat gluten films of various thicknesses formed at 30-70 C were treated with cold sulfuric acid to produce sulfated gluten films. Chemical, thermal, thermal stability, and water uptake properties were characterized for neat and sulfated films. The sulfated gluten films were able to absorb up to 30 times their weight in deionized water. However, this value dropped to 3.5 when the film was soaked in a 0.9% (w/w) NaCl solution. The films were also soaked 4 times in deionized water, and each soaking resulted in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…These results might indicate lower thermal stability of carboxylate groups in the modified samples. A previous study20 found similar results for gluten films modified with sulfuric acid. In that study, the sulfated gluten films showed rapid decreases in weights at ∼230°C.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…These results might indicate lower thermal stability of carboxylate groups in the modified samples. A previous study20 found similar results for gluten films modified with sulfuric acid. In that study, the sulfated gluten films showed rapid decreases in weights at ∼230°C.…”
Section: Resultssupporting
confidence: 74%
“…Wheat gluten has been used to produce completely natural superabsorbent materials 17–20. This involved reacting gluten with sulfuric17, 18, 20 or phosphoric acid 19. Sulfuric acid reacts with hydroxyl groups in amino acids of gluten, such as serine and tyrosine, to produce sulfuric acid esters.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies conducted to obtain WG films using mainly the casting technique have recently been reported [23,24,25,26,27,28]; the use of extrusion [29] and thermo-compression [30,31] has also been considered. However, there are no reports indicating the production of WG films with a thickness as small as those observed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…In prior research, we applied scanning electron microscopy (SEM) to 0.15 and 0.6 mm thick thermoformed films of native wheat gluten and wheat gluten that had been treated with sulfuric acid. Although the treatment created shallow craters in a surface that was smooth and craterless without acid treatment, these craters did not appear to penetrate into the interior and may be formed by partial dissolution of the gluten . Further, in recent research, we have applied SEM to dry wheat gluten in the seed and to dried samples of mixed or developed wheat dough and have found that dry gluten samples are generally amorphous and featureless and that the images reveal no information that relates to the hydrated properties of the gluten protein.…”
Section: Discussionmentioning
confidence: 99%
“…Vital wheat gluten has a free swelling capacity (FSC) for water of 1.4–1.5 and has been modified to produce superabsorbent materials. The modification occurs when native gluten is reacted with polyhydroxy acids such as sulfuric, citric acid, or phosphoric acid . The acid‐modified gluten samples were reported to absorb up to hundreds of times their weight in water.…”
Section: Introductionmentioning
confidence: 99%